Exploring Service Quality and Visitors’ Complaining Behavior of Nepalese Tourism Industry - Bhattarai, Bal Ram; Prompanyo, Manoch (Journal of Business and Management, 2022)
Background: Service quality and customer feedback are integral parts of any service organization. Creating the context to vent the visitors’ discomfort is a primary task for quality service delivery in the tourism industry. Objectives: This study aims to explore Nepalese tourism service quality and customers’ complaining behavior. Methods: A qualitative framework of in-depth interviews with tourism service providers, tourism experts, and visitors of the destination are the primary sources of data. Narrative manual content analysis has been adopted to analyze and draw the result from the data. Results: Nepalese tourism service quality has not been able to meet the visitor’s service expectations, however, some natural and provider’s experiences have made most of the visitors patronize the destination Nepal. Visitors are positing three types of complaining behaviors, the first category that generally goes for voice complaining from the service providers are labeled as redress seekers, the second category visitors cannot get an appropriate environment to vent the matter of dissatisfaction, the final category visitors do not like to share their matter of discomfort with the service providers. Conclusion: Nepalese tourism service demands much effort to make it more visitors friendly. Visitors must be provided with appropriate situations to express their matter of discomfort and match the expectations that they are seeking.